2011
DOI: 10.1177/0269215511419382
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of electromyographic biofeedback and electrical stimulation following arthroscopic partial meniscectomy: a randomized controlled trial

Abstract: The addition of electromyographic biofeedback training to a conventional exercise programme following arthroscopic partial meniscectomy helps to speed up the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 32 publications
0
67
0
Order By: Relevance
“…The results of this study showed that EMGBF training of the VMO increased the MVIC of the quadriceps, and this finding is consistent with that in the earlier studies. EMGBF training during isometric exercise provided the subjects with visual and auditory stimulation, which might have encouraged them to participate actively, resulting in improvement in the MVIC 39 ) . USBF training also improved the MVIC of the quadriceps in patients with knee OA, but we were unable to find any studies reporting the effects of USBF training on knee OA that could be compared with this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that EMGBF training of the VMO increased the MVIC of the quadriceps, and this finding is consistent with that in the earlier studies. EMGBF training during isometric exercise provided the subjects with visual and auditory stimulation, which might have encouraged them to participate actively, resulting in improvement in the MVIC 39 ) . USBF training also improved the MVIC of the quadriceps in patients with knee OA, but we were unable to find any studies reporting the effects of USBF training on knee OA that could be compared with this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, performing outpatient physical therapy plus home exercise was better than performing only home exercise, 24 and EMG biofeedback can be an important adjunct in the treatment of patients undergoing arthroscopic partial meniscectomy. 1 Most of the studies included in this review did not perform allocation concealment or blinding of the assessor; only 2 studies performed analysis by intention to treat, and 17 studies did not have an acceptable compliance. Of the 25 studies evaluated, 7 were excluded because the authors did not randomize or their control group did not undergo arthroscopic partial meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports highlighted EMG biofeedback as an efficacious therapeutic modality following menisectomy [8]. A recent randomized, single blind, clinical study suggested that the addition of EMG biofeedback to a conventional exercise programme resulted in a significantly shorter time in using a walking aid compared to conventional exercise training alone following arthroscopic partial meniscectomy [9]. In addition, the EMG biofeedback group demonstrated significantly better quadriceps femoris muscle strength and Lysholm Knee Scoring Scale scores than the home exercise and electrical stimulation groups.…”
Section: Physiological Biofeedbackmentioning
confidence: 99%